Recurrence rates of atrial fibrillation ablation according to body mass Index, a nationwide, registry-based danish study. (19th May 2022) - Toennesen, J; Pallisgaard, J; Rasmussen, PV; Ruwald, MH; Zoerner, CR; Gislason, G; Hansen, J; Johannessen, A; Worck, R; Hansen, ML
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Novo Nordisk supported the project. Background: The proportion of people with obesity is rapidly rising, and the number of overweight patients undergoing ablation for atrial fibrillation (AF) is also increasing. The link between body mass index (BMI), and AF prevalence is well-established but the impact of BMI on the risk of recurrent AF after ablation is less elucidated. Therefore, data pertaining to recurrence rates of ablations according to BMI in large, unselected cohorts of patients is still warranted. Purpose: To examine the risk of recurrent AF after AF ablation by BMI. Method: Using Danish nationwide registries, all Danish patients above 18 years who underwent first-time AF ablation from January 1st 2010 to December 31st 2018 were identified and included at the date of ablation. The patients were categorized by BMI; underweight: < 18.5 kg/m2; normal weight: 18.5-24 kg/m2; overweight 25-29 kg/m2; obese 30-34 kg/m2; morbidly obese > 34 kg/m2. Recurrent AF was defined using a composite endpoint comprising claimed prescriptions of anti-arrhythmic drugs, hospital admissions due to AF, re-ablation, or electrical cardioversions. The cumulative incidence of recurrent AF by BMI at 1- and 5-year follow-up after a blanking period of 90 days, was estimated using the Aalen-Johansen estimator, takin death as competing risk in to account. The relative rates of recurrent AF by BMI were examined using Cox models adjusted for sex, age, procedure-year, heart failure, ischemic heart disease, chronic obstructive pulmonary disease, chronic kidney disease, hypertension, and diabetes. Results: The study cohort consisted of 9, 229 patients. Median age [IQR] decreased from 64 [60, 75] in the normal weight group to 60 [53, 66] in the morbidly obese. The number of patients with a CHA2DS2-VASc score of 2 or more increased from 48% in normal-weight to 65% in morbidly obese. Use of amiodarone increased by BMI category, while the use of Class 1C anti-arrhythmic medication remained stable. Figures 1 and 2 show the 1- and 5-year cumulative incidence of recurrent AF, Hazard Ratios (HR), and 95% Confidence Intervals (CI 95%) stratified by BMI categories and depict that the risk of recurrent AF increased incrementally and significantly in overweight groups compared to normal weight patients, both in 1- and 5-year follow-up. Underweight patients demonstrated non-significantly increased risk of recurrent AF, both in 1- and 5-year follow-up. Conclusion: In this large nationwide study examining recurrent AF post AF ablation, we found that recurrence rates of AF increased incrementally according to BMI, both in short- and long-term follow-up. Therefore, aggressive weight management in overweight patients could potentially provide substantial benefits and improve short- and long-term outcomes after ablation.